Pengaplikasian Warna Foundation Terhadap Kulit Wajah Gelap Pada Rias Wajah Pesta - Muzakiyah Qurrata A'yuni; Hayatunnufus Hayatunnufus (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
AbstractThe difficulty in choosing Foundation colors is very influential for the makeup of one of them is makeup party. Because the wrong in choosing foundation colors make a striped face does not correspond to the skin color. The purpose of this study is to determine the difference in the foundation color application against the skin of dark face on party makeup.This type of research is a pseudo experiment (quasi experiment) with the research design of Non-Equivalent Control Group design. The inside object of the study is a woman who has a dark skin 18-25 years old with a sample number of 3 people. The data analysis techniques used are test normality, homogeneity test and Anava test.Based on the research result of foundation color application against the skin of dark face on party makeup seen from the foundation level grading indicators and the foundation color conformance level. Foundation color application Results One level brighter has an average level of smoothness 2.28 level of foundation color conformity has an average of 2.14. Foundation Color application Result one-level darker level of smoothness has an average of 2.14 foundation color conformity 2.28. The results of the application of two colors foundation one level lighter mixing with one level darker the level of smoothness has an average of 3.28 the foundation color conformity level has an average of 3.14. There is a foundation color difference against dark facial skin on party makeup at the foundation's smoothness level 5.029 > 3.55 and foundation color compatibility level 4.031 > 3.55. A suggestion to choose the appropriate foundation color that is one lighter level is mixed with one darker level. Keywords: color foundation, dark facial skin, makeup Party